2006
DOI: 10.1254/jphs.crj06003x
|View full text |Cite
|
Sign up to set email alerts
|

A Missing Link Between a High Salt Intake and Blood Pressure Increase

Abstract: Abstract. It is widely accepted that a high sodium intake triggers blood pressure rise. However, only one-third of the normotensive subjects were reported to show salt-sensitivity in their blood pressure. Many factors have been proposed as causes of salt-sensitive hypertension, but none of them provides a satisfactory explanation. We propose, on the basis of accumulated data, that the reduced activity of the kallikrein-kinin system in the kidney may provide this link. Renal kallikrein is secreted by the distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 152 publications
(144 reference statements)
5
28
0
Order By: Relevance
“…This observation might be a reflection on the utilization of kininogen to form BK, a proinflammatory agent as previously reported [35,36]. BK1R and BK2R antagonists may normalize the diabetic state in experimentally induced diabetes in mice [37]. Thus, BK antagonist may be targeted for use in diabetic disorders.…”
Section: The Bradykinin System and Diabetessupporting
confidence: 59%
“…This observation might be a reflection on the utilization of kininogen to form BK, a proinflammatory agent as previously reported [35,36]. BK1R and BK2R antagonists may normalize the diabetic state in experimentally induced diabetes in mice [37]. Thus, BK antagonist may be targeted for use in diabetic disorders.…”
Section: The Bradykinin System and Diabetessupporting
confidence: 59%
“…In these mice, the lack of B2 receptor from early development did not alter the maturation of blood pressure under conditions of normal sodium intake [25] . Interestingly, our results showed that human tissue kallikrein gene delivery in normal SD rats had no effect on the excretion of natrium from the kidney under normal sodium intake, although it has been known that renal KKS is involved in the excretion of natrium in the kidney [15] . The renal KKS is composed of renal kallikrein, its inhibitor (kallistatin), low molecular weight kininogen, 2 tubular-specific kinases, and kinin receptors.…”
Section: Discussionmentioning
confidence: 61%
“…Renal kallikrein is synthesized in the connecting tubule cells in the distal nephron, and is involved in the homeostasis of sodium and water balance in the kidney. Its attenuation is suggested as a possible etiological factor in salt-sensitive hypertension [15,16] . Our previous studies have demonstrated that rAAV-HK delivery attenuates the increased blood pressure induced by fructose or streptozotocin in conjunction with a high-fat diet and ameliorates organ injury [17] .…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence documenting the role of BK in the pathogenesis of hypertension (9)(10). The pharmacological actions of BK in regulation of systemic BP are vasodilation in most areas of circulation, reduction in total peripheral vascular resistance and regulation of sodium excretion from the kidney (11).…”
Section: Pathophysiological Roles Of Bradykinin System In Hypertensiomentioning
confidence: 99%